SURVEY TINGKAT PENGETAHUAN DAN KOMPETENSI GURU TENTANG TEKNOLOGI INFORMASI DAN KOMUNIKASI DI KABUPATEN GARUT - Mahmud, Mahmud; Darmawan, Deni; Suherman, Uman; Jamilah, Jamilah (Universitas Pendidikan Indonesia, 2017)
The study was based on the development of information and communication technology (ICT), which enters theworld of education. ICT developments are always dynamic, so teachers need to adapt every dynamicdevelopment of ICT. Master Islamic senior high schools in Garut regency reached 1281 people, so to see thelevel of knowledge and competence utilization of ICT-based learning media need proper research. The survey of1281 people taking population recorded as a teacher of Islamic senior high schools. The sample of this researchis 100 people. The level of competence of teachers in the use of media-based learning information andcommunication technologies have a considerable level. The relationship between the level of knowledge with thelevel of teacher competence Islamic senior high schools in Garut has a very strong correlation value. Based onthe results of the study, submitted suggestions that teachers Aliyah madrasas in Garut has a high potential in thedevelopment of teaching and learning. Thus, to obtain an increase in the need for knowledge of the authority ofthe government to hold trainings, workshops, etc., so that the quality of education will be more advanced.